2018
DOI: 10.1016/j.ijmedinf.2017.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Natural language processing of clinical notes for identification of critical limb ischemia

Abstract: The CLI-NLP algorithm for identification of CLI from narrative clinical notes in an EHR had excellent PPV and has potential for translation to patient care as it will enable automated identification of CLI cases for quality projects, clinical decision support tools and support a learning healthcare system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 38 publications
(48 reference statements)
1
50
0
Order By: Relevance
“…Past studies have demonstrated that NLP can be used to obtain valuable data for research that can be more accurate than ICD codes. [7,[24][25][26] This study supports these findings, identifying NLP as clearly superior for individual phenotype algorithms. As data volume and accuracy are critical for big data initiatives, it stands to reason that NLP-derived features will yield superior models for these endeavors.…”
Section: Discussionsupporting
confidence: 73%
“…Past studies have demonstrated that NLP can be used to obtain valuable data for research that can be more accurate than ICD codes. [7,[24][25][26] This study supports these findings, identifying NLP as clearly superior for individual phenotype algorithms. As data volume and accuracy are critical for big data initiatives, it stands to reason that NLP-derived features will yield superior models for these endeavors.…”
Section: Discussionsupporting
confidence: 73%
“…The results of this study indicate that existing clinical codes of DFU cannot be used to create a registry without supporting evidence, and alternative means should be sought. Natural language processing (NLP) of clinical notes was used to identify critical limb ischemia in the EMR of Mayo Clinic . NLP demonstrated a significantly higher PPV, and a similarly high sensitivity vs using ICD‐9 billing codes alone.…”
Section: Discussionmentioning
confidence: 99%
“…Because NLP pipelines and machine-learning approaches, in general, use expert-annotated text corpora with information coded by different experts, higher interrater reliability would increase the signal-to-noise ratio and, thus, improve semantic classification accuracy in natural free-text. In turn, NLP tools could be more effective in the identification of clinically relevant concepts hidden in clinical notes and corresponding biomedical literature and could be linked to computerized decision support systems for the implementation of evidence-based management strategies at the point of care [ 34 ].…”
Section: Discussionmentioning
confidence: 99%